Report on CGIAR Research in Africa Evaluation Survey - Katingi, E. (International Livestock Research Institute, 2009)
This report summarizes findings of the CGIAR Research in Africa survey conducted between September and October 2009. The map, a project database of the research projects carried out by CGIAR Centers in Africa was launched and made online to CG centers staff and other users in February 2009 with the aim of making research information publicly accessible to all CGIAR staff and other key stakeholders in the region in order to facilitate information sharing, promote partnership opportunities and collective action. Besides trying to get feedback from the users on the map, the survey also sought to establish the level of awareness on the map, harmonize the key primary areas of research as well identify new areas of improvement.